Hands-on experiential learning of structural mechanics. Issue 4 (2nd October 2019) - Haritos, Nicholas
ABSTRACT: An innovative and affordable table-top experiential learning platform, that aims to redress the lack of 'hands on' experimentation opportunities in engineering mechanics courses, is presented in this paper. Experiments developed for this platform are targeted for use by students working in pairs in practice class/tutorials sessions of subjects such as Statics, Mechanics of Solids/Materials/Structures, Introduction to Finite Element Modelling and Structural Dynamics. By blending hands-on experimentation in the practice class/tutorial classroom, student learning experience is enriched and retention of the basic principles of mechanics greatly enhanced. In addition, introducing on-line Smart Sparrow adaptive learning modules in combination with this platform enables students to pace and test their learning experience in mechanics to suit their own specific situation.